Altered Neuronal Responses During an Affective Stroop Task in Adolescents With Conduct Disorder - Fehlbaum, Lynn V.; Raschle, Nora M.; Menks, Willeke M.; Prätzlich, Martin; Flemming, Eva; Wyss, Letizia; Euler, Felix; Sheridan, Margaret; Sterzer, Philipp; Stadler, Christina (Frontiers in Psychology, 2018)
Conduct disorder (CD) is a psychiatric disorder of childhood and adolescence which has been linked to deficient emotion processing and regulation. The behavioral and neuronal correlates targeting the interaction of emotion processing and response inhibition are still under investigation. Whole-brain event-related fMRI was applied during an affective Stroop task in 39 adolescents with CD and 39 typically developing adolescents (TD). Participants were presented with an emotional stimulus (negative/neutral) followed by a Stroop task with varying cognitive load (congruent/incongruent/blank trials). fMRI analysis included standard preprocessing, region of interest analyses (amygdala, insula, ventromedial prefrontal cortex) and whole-brain analyses based on a 2(group) x 2(emotion) x 3(task) full-factorial ANOVA. Adolescents with CD made significantly more errors, while reaction times did not significantly differ compared to TD. Additionally, we observed a lack of downregulation of left amygdala activity in response to incongruent trials and increased anterior insula activity for CD relative to TD during affective Stroop task processing (cluster-level FWE-corrected (p<0.05)). Even though no three-way interaction (group x emotion x task) interaction was detected, the findings presented still provide evidence for altered neuronal underpinnings of the interaction of emotion processing and response inhibition in CD. Moreover, our results may corroborate previous evidence of emotion dysregulation as a core dysfunction in CD. Future studies shall focus on investigating the interaction of emotion processing and response inhibition in CD subgroups (e.g., variations in callous-unemotional traits, impulsivity, or anxiety).